Hypericin Enhances Paclitaxel-Induced B16-F10 Cell Apoptosis by Activating a Cytochrome c Release-Dependent Pathway - Liyun Sun; Zixuan Li; Huoli Shang; Xiujuan Xin (Frontiers Media S.A., 2021)
The enhanced inhibitory effect of paclitaxel (PTX) combined with hypericin (HY) on B16-F10 cells may be realized through the ROS-related cytochrome c release pathway. The apoptotic characteristics of the B16-F10 cells, such as DNA fragmentation, chromatin condensation, and apoptotic body formation, were all enhanced in the combined treatment group. Further investigation showed that the combination of paclitaxel and HY could increase the level of mitochondrial damage and the concentration of cytochrome c, causing the expression of caspase-3 and the cleavage of PARP.1. Compared with paclitaxel or HY alone, the level of reactive oxygen species (ROS) increased significantly, while glutathione reductase (GR) activity and intracellular glutathione (GSH) levels decreased significantly in the combination group.